Civilized Urbanity. Modernismo and the Urban Landscape - Angela Martin Pérez (Catedral Tomada: Revista de Crítica Literaria Latinoamericana, 2017)
In this essay, I examine the inclusion of the civilization/barbarism binary in the literature of modernistas writers. To this end, I will briefly analyze the historic contexts after the independence of the colonies and the new neo-imperialist order that settled in the city and demanded social, economic and urban changes that affected the entire social strata. At the same time, I will explain how the formation of a new citizen was undertaken, as it had to follow certain behavioral guidelines to isolate itself from barbarism and savagery of places far away from the metropolis. With it I will justify the importance of the so-called ciudad letrada (city of letters) in the formation of new modern nations and describe the birth of the modernist writer, self-defined by its individuality and the contradictions involved in its writing. I will explain my arguments with the texts that, born in the process of modernity, claim the tradition of denying the capitalist utilitarian society into which they are inserted.